2012
DOI: 10.1111/j.1365-3180.2012.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactants and the kinetic energy of monodroplets on the deposit structure of glyphosate at the micro‐scale and their relevance to herbicide bio‐efficacy on selected weed species

Abstract: Summary The deposit pattern of foliar‐applied agrochemicals, and its relation to their bio‐efficacy, has major practical importance. Thus, in our experiments, we evaluated the relevance of the deposition properties of glyphosate for its bio‐efficacy. The deposition pattern of glyphosate monodroplets was influenced by using surfactant and by applying the droplets with or without kinetic energy to the plant foliage. Monodroplets (1 μL) of glyphosate, formulated with or without ethoxylated rapeseed oil surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The aim of this article was to suggest means by which this ring shape could be eliminated or at least reduced. It has previously been shown that the coffee‐ring formation can be suppressed by introducing surfactant driven Marangoni flow, altering DLVO interactions, using electrowetting, changing particle shape or through careful selection of an electric field . However, none of these are ideal for P‐OLED applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this article was to suggest means by which this ring shape could be eliminated or at least reduced. It has previously been shown that the coffee‐ring formation can be suppressed by introducing surfactant driven Marangoni flow, altering DLVO interactions, using electrowetting, changing particle shape or through careful selection of an electric field . However, none of these are ideal for P‐OLED applications.…”
Section: Resultsmentioning
confidence: 99%
“…There are a vast number of systems for which evaporation of a droplet, containing a nonvolatile component is relevant. The distribution of pesticide on leaves is important when attempting to kill weeds . There are several biological applications, for example DNA microarrays, blood residue analysis for disease diagnostics and crime scene reconstruction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods which have been shown to at least reduce the extent of coffee-ring formation are in abundance. A surfactant can be introduced to initiate a Marangoni flow that counteracts the capillary flow [8,19]. An electric field can be chosen to tailor film shape, as shown by Wray et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the array of industrial and practical applications for which drying is an important step. There are several applications for biological fluids [1], including pattern analysis of dried blood, for crime scene investigation [2] and disease diagnostics [3], DNA microarrays [4][5][6][7] and herbicides/pesticides on leaves [8]. In addition, micro/nano electronics can be manufactured [9][10][11][12][13][14] diode displays (P-OLEDs) [15].…”
Section: Introductionmentioning
confidence: 99%